The triumph of the sun a novel of african adventure - Smith, Wilbur (London Macmillan, 2005)
1884 and in Khartoum, on the banks of the Nile, the Courtneys meet the Ballantynes in this epic adventure from one of the world's most celebrated novelists
1
Keywords: English Fiction